Islamic Geometric Design: By Eric Broug (New York: Thames & Hudson, 2013. 256 pages full color.) (American Journal of Islam and Society, 2015)
The subject of Islamic geometric design has been described in numerous ways:Keith Critchlow’s Islamic Patterns and Syed Jan Abbas and Amer ShakerSalman’s Symmetries of Islamic Geometrical Patterns, both highly esotericinterpretations; Owen Jones’ Grammar of Ornament, Emile Prisse d’Avennes’L’Art arabe d’apres les monuments du Kaire, and Jules Bourgoin’s ArabicGeometrical Pattern and Design, all descriptions of drawing collections; andeven as a theme for countless “coffee table” books resplendent with glossyphotographs of exotic patterns and colors.Is it fair to evaluate this book without tending to imagine the previouscategories of this study? Years ago I led a course on this topic and desperatelytried to juggle the beautiful, historic, and hands-on practical manifestationsof the sacred through drawing particular geometric patterns over and over again. For this course I needed to select chapters, or portions of the abovementionedtexts in addition to the comprehensive works of K. A. Creswellin Early Muslim Architecture, Doris Behrens-Abou Seif’s Mamluks of Cairoand Minarets of Cairo, as well as other architectural studies, and interpretand reconstruct the designs in order to teach them. It was a research projectof sorts where the outcome was not textual but pedagogical.While reading this text by Eric Broug, I felt that he had gone through asimilar but far more prolonged process. His book stands alone for severalreasons: the author (1) weaves knowledge of the historical, recognition ofthe beautiful, and reconstruction of the practical regarding patterns. The succinctexplanatory text, incredible detailed photography in situ, and clear stepby-step diagrams converge to elucidate this rich material; (2) outlines theinfluence of other artistic traditions and the development of a clear type of“Islamic geometry” that is easily recognizable; and (3) concentrates on thedesign approach of craftspeople, which was separate and concurrent with thescientific study of geometry. This difference is important: craftspeople appliedgeometric patterns to various surfaces and were concerned with aestheticcompositions; whereas scientists contemplated the complex patternsin terms of mathematical geometries ...